Analisis Risiko Pembangunan Mandalika Urban and Tourism Infrastructure Project Kawasan Ekonomi Khusus Mandalika - Wawan Setiawan; Henny Pratiwi Adi; Rifqi Brilyant Arief (Journal of Mandalika Literature, 2025)
This research aims to identify and assess the risks associated with the Mandalika Urban and Tourism Infrastructure Project (MUTIP) in the Mandalika Special Economic Zone (SEZ). The research methodology involves collecting secondary and primary data using risk identification techniques such as interviews and brainstorming. Data is then processed using likelihood and consequences scales to identify dominant risks and design effective mitigation strategies. The study's findings indicate that prominent risks include difficulties in land acquisition, unforeseen functional costs, and potential non-payment by guests. The results of the questionnaire-based research identify three main risks of concern to respondents: contractor credibility (40%), insufficient revenue from visitors (36.67%), and disturbances from the community (33.33%). These findings highlight the significant concern of respondents regarding critical factors that could impact the success of the project. This insight is crucial for project planning and risk mitigation.